Implementation of Corporate Social Responsibility and its Challenges for Banks in Swaziland - Nhlabatsi, Danger (2009)
Business firms employ different processes of social responsiveness to address social problems; they choose activities that are relevant to their interests, operations, and actions (Wood, 1991). This comes after the public has raised concerns that as business firms make profit from the communities, they should also be socially responsible to the communities from which they get the profits. As such, globalization has driven the Corporate Social Responsibility (CSR) concept throughout the world including Africa (Gjølberg, 2009). This research therefore, looked at the CSR practices by banks in Swaziland and the influence the practices have on clients and employees. The drivers of CSR were also examined to get a deeper understanding of the CSR practices and their challenges. In-depth telephone interviews were used to collect information on the CSR by banks in Swaziland. The study reveals that government and NGOs have no influence on CSR by banks in the country as they are hardly involved in the CSR activities. The research indicates that CSR by banks is motivated by creation of self image and gaining of recognition by the communities. International banks use their group policy as a base for CSR initiative in Swaziland. Limited budget is currently the only challenge for bank CSR as the need in communities is ever increasing. However, the unavailability of regulations on CSR leads to CSR concept not being clearly understood by companies and the society in Swaziland, which can lead to unclear responsibilities of companies under the banner of CSR and also raise unrealistic expectations by the society. The study calls for government to encourage companies to adopt CSR, and have the CSR in Swaziland being properly coordinated.